Sharing Pictures, Bridging Barriers: The Use of Photovoice to Increase Awareness of Women Refugees Issues in Jakarta - Adinia, Nissa Cita; Kirana, Chandra (UI Scholars Hub, 2019)
This paper is the implementation of Photovoice with women refugees from Roshan Learning Center, an education space for refugees and asylum seekers in Jakarta. Photovoice is one of participatory action research method which is designed to encourage participants to identify and represent their community strength and issues through photographs. This paper describes the result of Photovoice project done with 9 (nine) women refugees members of Roshan Learning Center, in Jakarta. The project aims to explore issues related to women refugees living in a metropolitan Jakarta. Jakarta is interpreted as a place full of social problems such as traffic and poverty. However, on the other hand, this situation also provided sense of independence for women. Participation in the Photovoice project gives multiple opportunities for reflection and somewhat ignite critical thinking. Such opportunities included deciding what to photograph, developing of why it was important, experiencing the group, as well as creating and participating in a group reflection. There were limitations on the implementation of the method, nevertheless, throughout 3 (three) common themes: struggle and challenges, finding strength, and hope, showed Photovoice project have succeeded in increasing students' understanding and concern for issues related to displacement and women refugees in Jakarta.